The development of novel auxetic woven structure for impact applications. Issue 7 (3rd July 2017) - Liaqat, Muhammad; Samad, Hafiz Abdul; Hamdani, Syed Talha Ali; Nawab, Yasir
Abstract: Nowadays, the auxetic materials, auxetic reinforcement as well as auxetic composite are under the great attention of scientific research due to having excellent mechanical properties. In the current research work, the impact resistance of composite was improved by modifying the four layer through the thickness woven structure, that was used as reinforcement. A comparison was made between the standard four layer through the thickness and modified four layer through the thickness woven structure in terms of auxeticity and penetration. The modified four layer through the thickness woven structure showed auxetic behavior in both warp and weft direction having less penetration resistance as compared to standard sample. The four layer through the thickness non-auxetic woven structures and modified auxetic four layer thorough the thickness woven structures were used as reinforcements to develop composite for impact resistance comparison. The result showed that impact resistance of auxetic composite was 6.7% greater as compared to the non-auxetic composite. It was concluded that the greater value of impact resistance was due to the auxetic behavior of modified four layer through the thickness woven structure.